Detection of human immunodeficiency virus type 1 (HIV-1) in urine cell pellets from HIV-1-seropositive individuals. - Li, J J (1992)
Fresh urine pellets from human immunodeficiency virus type 1 (HIV-1)-seropositive individuals were examined for the presence of the HIV-1 genomic sequence and gene products. By using the polymerase chain reaction technique, HIV-1 DNA proviral sequences were detected in 53 of 80 (66.25%) fresh urine pellets from HIV-1-seropositive individuals, while urine pellets from all 24 healthy heterosexual controls were negative. HIV-1 RNA in urine pellets was detected by reverse transcriptase polymerase chain reaction in 2 of 43 (4.7%) HIV-1-seropositive individuals. In addition, HIV-1 p24 core antigen was demonstrated in 3 of 80 urine pellets from HIV-1-seropositive individuals by enzyme-linked immunosorbent assay. Moreover, HIV-1 p24 core antigen and HIV-1 RNA were shown in the cellular component of urine pellets from HIV-1-seropositive individuals by immunohistochemical staining and in situ hybridization. These results indicate that HIV-1 can be present in urine pellets from HIV-1-infected individuals.